Pengaruh Lingkungan Fisik Kelas Dan Dukungan Orang Tua Terhadap Motivasi Belajar SMPN 1 Liukang Tangaya - Adriyani; Muh Yahya; Elpisah (Jayapangus Press, 2022)
Education is said to be successful if students are able to motivate themselves in learning. The purpose of this study was to look at the influence of the school's physical environment and parental support on learning motivation at State Junior High School 1 Liukang Tangaya. This type of quantitative research uses a correlative descriptive approach. The population of all 5th graders, as many as 72 people. The study sample used (Probability Sampling) so that the sample was a 5/A grader, totaling 25 students. Collection of observational data, and dissemination of questionnaires. Data analysis uses quantitative data. The results showed that: the physical environment of the classroom and parental support have an effect on the motivation of learning students at SMPN 1 Liukang Tangaya. Conclusions at State Junior High School 1 Liukang Tangaya, the physical environment of the class affects the student's learning motivation, but parental support has no effect on the student's learning motivation.